Processing figurative language: Evidence from native and non-native speakers of English - Alkhammash, Reem (Frontiers in Psychology, 2022)
In recent research on figurative phrases, factors (e.g., familiarity, transparency, meaning, and decomposability) have played a significant influence on how native and non-native English speakers (various L1 and L1 Arabic) acquire, process, and comprehend figurative language. These factors are not always described and operationalized precisely, and are frequently considered autonomous. Following the same path as Carrol et al. (2018), this study explores these factors in terms of language users’ ratings and their abilities to accurately infer meaning from a variety of familiar English and translated idioms and novel metaphors. A total of 123 participants from various language groups engaged in this study. The findings showed that familiarity is a strong predictor of transparency. In the ability to infer the meaning correctly, the best-fit model included an interaction between transparency and familiarity. The findings showed that guessing the meaning correctly led to a greater increase in the scores of transparency and decomposability. We explore how these factors work together to enable speakers to infer the meaning of both known and new figurative words at various levels. These results have significant implications for the learning and teaching of figurative phrases in the EFL context, as they indicate variables that may make a figurative phrase valuable in terms of teaching time and effort.